The Role of Flight Instructors in Building Safety Culture among Student Pilots at API Banyuwangi - Cahyo, Dimas Hari; Rumani, Daniel Dewantoro; Kurniawanto, Hari; Chairustakmal (Jurnal Informatika Ekonomi Bisnis, 2025)
Safety culture in aviation training is fundamentally shaped by the interpersonal and instructional behaviors of flight instructors. Instructors not only deliver technical content but also model risk awareness, communication norms, and emotional discipline that shape how student pilots internalize safety values. This literature-based analysis focuses on flight training practices at API Banyuwangi and identifies three core mechanisms that drive safety culture development: instructor competence, leadership style, and institutional reinforcement. Competent instructors who demonstrate reflective pedagogy and consistent behavioral modeling are shown to foster higher levels of psychological safety and long-term risk accountability among trainees. Moreover, institutions that integrate safety objectives across curricula, performance evaluations, and infrastructure further amplify these effects. The synthesis highlights that effective safety education emerges from the convergence of individual instructional capacity and organizational alignment. Embedding safety as a shared ethos rather than a procedural obligation requires intentional design at both the pedagogical and institutional levels.